Marking material of ceramic body inductor, manufacturing method and ceramic body inductor
By using ceramic substrates and amorphous materials in component identification materials, and using ball milling and sintering processes, the problem of easy wear or falling off in the production process is solved, and a more stable and efficient identification of identification materials is achieved.
Patent Information
- Application Number
- CN202411979237.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Existing component identification materials are susceptible to collision and extrusion deformation during the production process, resulting in the identification wear or fall off, and lose the function of identifying product direction.
Ceramic substrates Al2O3 and SiO2 are used as main components, and amorphous materials and coloring materials with low densification temperature are added to prepare marking materials through ball milling and sintering processes to improve sintering density and wettability with ceramic materials.
The combination of the mark and components is improved, making the mark more stable and not easy to wear or fall off, while ensuring that the mark can be effectively identified.
Smart Images

Figure CN119797901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to electronic components, and in particular to a marking material for a ceramic inductor, a manufacturing method and the ceramic inductor. Background Art
[0002] Due to their wide range of uses, components are usually used in a variety of structural types to achieve characteristic function requirements. Since product design and production usually show differences in directionality, inductance and polarity, the outermost surface of electronic components is marked to distinguish the inductance direction during testing and the product placement direction during packaging through color and appearance to maintain product consistency and reduce usage deviations caused by product polarity. In the existing component process, in order to ensure that the product direction can be effectively identified, the mark is usually placed on the outermost side of the magnet. However, due to collisions with each other during product production, or extrusion and deformation between the equipment, the mark may be worn and damaged. In severe cases, the entire surface may fall off, resulting in the loss of the function of identifying the product direction.
[0003] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0004] The main purpose of the present invention is to overcome the defects existing in the above-mentioned background technology and provide a marking material, a manufacturing method and a ceramic inductor for a ceramic inductor.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A marking material for a ceramic inductor, comprising a ceramic substrate Al 2 O 3 16-28wt%, SiO 2 22-33wt%, diethylene glycol butyl ether 14-21wt%, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide 1-7wt%, an amorphous material containing B, Si, O and K 16-23wt%, and a coloring material 4-6wt%.
[0007] Furthermore, the amorphous material containing B, Si, O and K is B and K co-doped borosilicate glass.
[0008] Furthermore, the coloring material includes one or more compounds of Co, Fe, Cr, Mn, and Cu.
[0009] Furthermore, the coloring material contains 1.2-2wt% of cobalt oxide, 1.2-1.3wt% of iron oxide, 0.9-1.2wt% of copper oxide, 0.6-1.2wt% of manganese oxide, and 0.01-0.02wt% of chromium oxide.
[0010] Furthermore, the ceramic substrate comprises a mixture or a composite of Al2O3 and SiO2 with a particle size of 2 to 3 μm and a maximum particle size of ≤5 μm.
[0011] Furthermore, the ceramic substrate also includes nano-scale silicon dioxide.
[0012] A method for manufacturing the identification material of the ceramic inductor comprises the following steps:
[0013] S1: Prepare the raw materials of the marking material, including the ceramic substrate Al 2 O 3 15-25 wt%, SiO 2 20-30wt%, organic auxiliary acrylic resin 6-12wt%, diethylene glycol butyl ether 13-19wt%, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide 1-6wt%, amorphous material containing B, Si, O and K 15-21wt%, and coloring material 4-5wt%;
[0014] S2: The mixed raw materials are processed by ball milling process to obtain a marking material precursor, and the obtained marking material precursor is subjected to a subsequent sintering process to obtain a marking material.
[0015] Furthermore, in step S2, the marking material raw material is poured into a ball mill for ball milling to make the particle size D50 of the slurry ≤ 2.5 μm, and then dried and kept warm at 40° C. to 100° C. for 3 min to 20 min and then ground to obtain the marking material.
[0016] A ceramic inductor has a logo made of the logo material of the ceramic inductor.
[0017] Furthermore, a first identification layer is provided on the substrate layer on the upper surface of the inductor;
[0018] The inner dielectric layer of the inductor corresponding to the first identification layer is provided with at least one intermediate identification layer;
[0019] A second identification layer is provided on the substrate layer on the lower surface of the inductor corresponding to the middle identification layer;
[0020] Among them, the substrate layer on the upper surface of the inductor provided with the first identification layer, the dielectric layer on the middle identification layer, and the substrate layer on the lower surface of the inductor provided with the second identification layer are combined, stacked and sintered in sequence in the order of top, middle and bottom, so that the first identification layer, the middle identification layer and the second identification layer are combined to form an integrated identification pattern.
[0021] The present invention has the following beneficial effects:
[0022] The present invention provides a component identification material that can ensure that the identification of components is effectively identified and has good stability. By adding amorphous materials and coloring materials with low densification temperatures to a ceramic substrate, the sintering density and wettability with ceramic materials are improved, so as to improve the bonding force between the identification and the component so that they are tightly combined and not easily worn or fall off. The above-mentioned identification material contains a ceramic substrate containing Al and Si, an organic additive containing C, H, O, and P, an amorphous material containing B, Si, O, and K, such as borosilicate glass containing B, Si, O, and K, and a coloring filler containing elements such as Co, Cr, Fe, Mn, and Cu. Adding the above-mentioned components to the ceramic substrate can promote the sintering of the ceramic material, wherein B, Si, and K can promote the low-temperature sintering of the ceramic body, form a low-melting-point phase, and promote the growth of ceramic particles. At the same time, by lowering the sintering temperature, the sintered particle size is reduced, and Fe, Mn, Cu, etc. can play a dissolution-promoting role, thereby achieving the purpose of lowering the sintering temperature.
[0023] From the experimental test results, compared with the logo made of existing logo materials, the logo of the embodiment of the present invention is more stable. In the test, the impact energy can be better absorbed by the material of the present invention, and the logo can be effectively identified while ensuring stability and not falling off; and for the logo with only the upper and lower bottom surfaces at the same time, the logo design of the present invention is also more stable and can play a good stabilizing role.
[0024] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of a ceramic inductor and its markings according to an embodiment of the present invention.
[0026] Figure 2 FIG. 4 is a flow chart of a ceramic inductor manufacturing process according to an embodiment of the present invention. DETAILED DESCRIPTION
[0027] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0028] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element. In addition, connection can be used for fixing as well as for coupling or communication.
[0029] It should be understood that the orientation or position relationship indicated by terms such as "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0031] The present invention provides a marking material for a ceramic inductor, which can effectively ensure the identification and stability of component markings. The material is composed of a ceramic substrate, an amorphous material with a low densification temperature and a coloring material, wherein the ceramic substrate contains Al and Si, the organic additive contains C, H, O, and P, the amorphous material contains B, Si, O, and K, and the coloring material contains elements such as Co, Cr, Fe, Mn, and Cu. The addition of these components promotes the sintering of the ceramic material, reduces the firing temperature, and enhances the bonding force between the marking and the component, making it less likely to wear or fall off. Experimental results show that the marking material of the present invention performs more stably in impact tests, can better absorb impact energy, ensures that the marking does not fall off and can be effectively identified, and improves the stability of the marking.
[0032] The embodiment of the present invention provides a marking material for a ceramic inductor, comprising a ceramic substrate Al 2 O 3 16-28wt%, SiO 2 22-33wt%, diethylene glycol butyl ether 14-21wt%, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide 1-7wt%, an amorphous material containing B, Si, O and K 16-23wt%, and a coloring material 4-6wt%.
[0033] In some embodiments, the amorphous material containing B, Si, O and K is B and K co-doped borosilicate glass.
[0034] In some embodiments, the coloring material comprises one or more compounds of Co, Fe, Cr, Mn, and Cu.
[0035] In some embodiments, the coloring material comprises 1.2-2 wt % of cobalt oxide, 1.2-1.3 wt % of iron oxide, 0.9-1.2 wt % of copper oxide, 0.6-1.2 wt % of manganese oxide, and 0.01-0.02 wt % of chromium oxide.
[0036] In some embodiments, the ceramic substrate includes a mixture or a composite of Al2O3 and SiO2 with a particle size of 2 to 3 μm and a maximum particle size of ≤5 μm.
[0037] In some embodiments, the ceramic substrate further comprises nano-sized silicon dioxide.
[0038] A method for manufacturing the identification material of the ceramic inductor comprises the following steps:
[0039] S1: Prepare the raw materials of the marking material, including the ceramic substrate Al 2 O 3 15-25 wt%, SiO 2 20-30wt%, organic auxiliary acrylic resin 6-12wt%, diethylene glycol butyl ether 13-19wt%, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide 1-6wt%, amorphous material containing B, Si, O and K 15-21wt%, and coloring material 4-5wt%;
[0040] S2: The mixed raw materials are processed by ball milling process to obtain marking materials.
[0041] Furthermore, in step S2, the marking material raw material is poured into a ball mill for ball milling to make the particle size D50 of the slurry ≤ 2.5 μm, and then dried and kept warm at 40° C. to 100° C. for 3 min to 20 min and then ground to obtain a marking material precursor. The obtained marking material precursor is subjected to a subsequent sintering process to obtain the marking material.
[0042] A ceramic inductor has a logo made of the logo material of the ceramic inductor.
[0043] like Figure 1As shown, in one embodiment, a first identification layer 2 is provided on a substrate layer 1 on the upper surface of the inductor; at least one intermediate identification layer 4 is provided on a dielectric layer 3 inside the inductor corresponding to the first identification layer 2; a second identification layer 6 is provided on a substrate layer 5 on the lower surface of the inductor corresponding to the intermediate identification layer 4; wherein, the substrate layer 1 on the upper surface of the inductor provided with the first identification layer 2, the dielectric layer 3 provided with the intermediate identification layer 4, and the substrate layer 5 on the lower surface of the inductor provided with the second identification layer 6 are sequentially combined, superimposed, and sintered in the order of top, middle, and bottom, so that the first identification layer, the intermediate identification layer, and the second identification layer are combined to form an integrated identification pattern.
[0044] The specific embodiments and experimental verification of the present invention are further described below.
[0045] The present invention provides a component identification material that can ensure that the identification of components is effectively identified and has good stability. By adding amorphous materials and coloring materials with low densification temperatures to a ceramic substrate, the sintering density and wettability with ceramic materials are improved, so as to improve the bonding force between the identification and the component so that they are tightly combined and not easily worn or fall off. The above-mentioned identification material contains a ceramic substrate containing Al and Si, an organic additive containing C, H, O, and P, an amorphous material containing B, Si, O, and K, such as borosilicate glass containing B, Si, O, and K, and a coloring filler containing elements such as Co, Cr, Fe, Mn, and Cu. Adding the above-mentioned components to the ceramic substrate can promote the sintering of the ceramic material, wherein B, Si, and K can promote the low-temperature sintering of the ceramic body, form a low-melting-point phase, and promote the growth of ceramic particles. At the same time, by lowering the sintering temperature, the sintered particle size is reduced, and Fe, Mn, Cu, etc. can play a dissolution-promoting role, thereby achieving the purpose of lowering the sintering temperature.
[0046] A method for preparing a colored marking material with the above ceramic body as a substrate mainly comprises the following steps:
[0047] S1. Prepare the raw materials of the marking material, including the following components in percentage by weight: ceramic main phase Al 2 O 3 15-25wt%, SiO 2 20-30 wt%, organic auxiliary acrylic resin 6-12 wt%, diethylene glycol butyl ether 13-19 wt%, diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide 1-6 wt%, amorphous material containing B, Si, O and K 15-21 wt%, and coloring material 4-5 wt%. When the weight percentage content is within this range, the relevant performance of the logo can be better. The ceramic substrate particle size is 2 to 3 μm and the maximum particle size is <5 μm. 2 O 3 、SiO 2 Material.
[0048] S2. Pour the mixed raw materials into a ball mill, and perform ball milling for 4 hours at a weight ratio of raw materials: zirconium oxide balls: anhydrous ethanol = 1:5:1.2, so that the particle size D50 of the slurry is less than 2.5 μm, and then dry and grind to obtain a marking material precursor.
[0049] The obtained marking material precursor is subjected to a subsequent sintering process to obtain a marking material, including a ceramic substrate Al 2 O 3 16-28wt%, SiO 2 22-33wt%, diethylene glycol butyl ether 14-21wt%, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide 1-7wt%, an amorphous material containing B, Si, O and K 16-23wt%, and a coloring material 4-6wt%.
[0050] Example 1
[0051] S1, in terms of mass percentage, the raw materials include Al 2 O 3 20wt%, SiO 2 30wt%, 11wt% of organic auxiliary acrylic resin, 13wt% of diethylene glycol butyl ether, 5wt% of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 17wt% of amorphous material containing B, Si, O and K, 1.2wt% of cobalt oxide, 1.2wt% of iron oxide, 0.9wt% of copper oxide, 0.69wt% of manganese oxide, and 0.01wt% of chromium oxide, wherein the particle size of nano-scale silicon dioxide is about 50nm, the particle size of the ceramic substrate is 2-3μm, and the maximum particle size is less than 5μm;
[0052] S2, weigh each raw material according to the mass ratio and pour it into a ball mill, with the ratio of raw material: zirconium oxide ball: anhydrous ethanol = 1:5:1.2 and ball mill at a speed of 200-250r / min for 4h, so that the particle size D50 of the slurry is less than 2.5μm, dry and keep warm at 40℃~100℃ for 3min~20min, and then grind to obtain the marking material. Through the reasonable proportion of the components, the specific content of iron oxide, cobalt oxide, copper oxide and manganese oxide in S1 are selected as colorants, and combined with other raw materials, the obtained marking material precursor is black. The obtained marking material precursor is subjected to a subsequent sintering process to obtain the marking material.
[0053] Example 2
[0054] S1, in terms of mass percentage, the raw materials include Al 2 O 3 25wt%, SiO 225wt%, 8wt% of organic auxiliary acrylic resin, 17wt% of diethylene glycol butyl ether, 4wt% of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 17wt% of amorphous material containing B, Si, O and K, 1.2wt% of cobalt oxide, 1.2wt% of iron oxide, 0.9wt% of copper oxide, 0.69wt% of manganese oxide, and 0.01wt% of chromium oxide, wherein the particle size of nano-scale silicon dioxide is about 50nm, the particle size of the ceramic substrate is 2-3μm, and the maximum particle size is less than 5μm;
[0055] S2. Weigh each raw material according to the mass ratio and pour it into a ball mill, with the ratio of raw material: zirconium oxide ball: anhydrous ethanol = 1:3:0.72 and ball mill at a speed of 150-200 / min for 3 hours, so that the particle size D50 of the slurry is less than 2.5 μm, dry and keep warm at 40°C-100°C for 3min-20min, and then grind to obtain the marking material precursor. The obtained marking material precursor is subjected to a subsequent sintering process to obtain the marking material.
[0056] Example 3
[0057] S1, in terms of mass percentage, the raw materials include Al 2 O 3 20wt%, SiO 2 28wt%, 11wt% of organic auxiliary acrylic resin, 15wt% of diethylene glycol butyl ether, 5wt% of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 17wt% of amorphous material containing B, Si, O and K, 1.2wt% of cobalt oxide, 1.2wt% of iron oxide, 0.9wt% of copper oxide, 0.69wt% of manganese oxide, and 0.01wt% of chromium oxide, wherein the particle size of nano-scale silicon dioxide is about 50nm, the particle size of the ceramic substrate is 2-3μm, and the maximum particle size is less than 5μm;
[0058] S2. Weigh each raw material according to the mass ratio and pour it into a ball mill, with the ratio of raw material: zirconium oxide ball: anhydrous ethanol = 1:4:1.5 and ball mill at a speed of 250-300r / min for 3h, so that the particle size D50 of the slurry is less than 2.5μm, dry and keep warm at 40℃-100℃ for 3min-20min, and then grind to obtain the marking material precursor. The obtained marking material precursor is subjected to a subsequent sintering process to obtain the marking material.
[0059] Application of the marking materials of Examples 1-3
[0060] Components production
[0061] The low temperature co-fired ceramic material is subjected to the processes of tape casting, punching, printing, stacking, laminating, sintering, chamfering, sealing and sintering to obtain a multilayer inductor component. The specific process includes:
[0062] 1. Ingredients: ① Casting slurry: slurry for forming ceramic inductors; ② Printing slurry: ink slurry for printing internal electrodes, logos, etc.
[0063] 2. Casting: The casting slurry is formed into a film of a certain thickness by casting.
[0064] 3. Opening holes: Open holes in the film formed by cast film to form through holes connecting the layers.
[0065] 4. Printing: Print the required internal electrodes, identification layer, etc. on the film.
[0066] 5. Lamination: The printed films are stacked layer by layer in sequence through a certain lamination process.
[0067] 6. Isostatic pressing: further press the layers together.
[0068] 7. Cutting: Cut the Bar block green body into product green body particles.
[0069] 8. Debinding: Cut the green pellets and put them into the debinding furnace to discharge part of the colloid first to reduce the glue content, mainly discharging low-boiling point and medium-boiling point organic solvents.
[0070] 9. Sintering: The debinding green body is subjected to heat treatment so that the powders in the green body react with each other to form a whole.
[0071] 10. Chamfering: Add grinding media, small balls, etc. to the sintered product for grinding, and slowly grind its corners / edges to make them smooth.
[0072] 11. Silver dipping: Apply conductive paste to both ends of the product to connect the internal coil and the external circuit of the product.
[0073] 12. Silver burning: The silver paste applied to both ends of the product during terminal electrode forming is subjected to high temperature heat treatment to form a dense whole.
[0074] 13. Electroplating: The product with terminal electrode package is surface treated again, and then Ni protective layer and Sn solder layer are electroplated in sequence.
[0075] 14. Appearance: Screen and separate products that meet the specifications and those that exceed the specifications.
[0076] 15. Sorting: Screen and separate products whose electrical properties meet certain requirements and those that exceed the specifications.
[0077] 16. Taping: Pack the products that have passed the appearance, size, electrical properties and reliability inspection in paper tape or plastic tape of general standard specifications, and roll up the woven products with plastic pulleys to complete the packaging.
[0078] Logo production
[0079] In the process of manufacturing ceramic inductor components, the method of making the logo is exemplified as follows. A first logo layer is set on the substrate layer on the upper surface of the component; at least one intermediate logo layer is set on the dielectric layer inside the component corresponding to the first logo layer; a second logo layer is set on the substrate layer on the lower surface of the component corresponding to the intermediate logo layer; the substrate layer on the upper surface of the component provided with the first logo layer, the dielectric layer provided with the intermediate logo layer, and the substrate layer on the lower surface of the component provided with the second logo layer are sequentially combined, stacked, and sintered in the order of top, middle, and bottom, so that the first logo layer, the intermediate logo layer, and the second logo layer are combined to form an integrated logo pattern. For specific processes and structures, reference can be made to the contents disclosed in the prior patent application CN 114218691 A.
[0080] Comparative experiment
[0081] Table 1 shows the comparative experimental data of Rockwell hardness, bending strength and impact test of the colored marking materials prepared in Examples 1-3 and the prior art. Among them, the impact test was conducted using multiple different impact forces.
[0082] Table 1
[0083]
[0084] It can be seen from the experimental test results that compared with the logo made of existing logo materials, the logo of the embodiment of the present invention is more stable. In the 3.5T / 8s lamination test of Example 1, the impact energy can be better absorbed by the material of the present invention, and the logo can be effectively identified while ensuring stability and not falling off. Examples 2-3 also have similar effects; and, for logos that only have upper and lower bottom surfaces at the same time, the logo design of the present invention is also more stable and can play a good stabilizing role.
[0085] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A marking material for a ceramic inductor, characterized in that it includes 16-28wt% of a ceramic substrate Al2O3, 22-33wt% of SiO2, 14-21wt% of diethylene glycol butyl ether, 1-7wt% of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 16-23wt% of an amorphous material containing B, Si, O and K, and 4-6wt% of a coloring material.
2. The marking material for ceramic inductor according to claim 1, characterized in that: The amorphous material containing B, Si, O and K is B and K co-doped borosilicate glass.
3. The marking material for ceramic inductor according to claim 1 or 2, characterized in that: The coloring material includes one or more compounds of Co, Fe, Cr, Mn, and Cu.
4. The marking material for ceramic inductor according to claim 3, characterized in that: The coloring material contains 1.2-2 wt % of cobalt oxide, 1.2-1.3 wt % of iron oxide, 0.9-1.2 wt % of copper oxide, 0.6-1.2 wt % of manganese oxide, and 0.01-0.02 wt % of chromium oxide.
5. The marking material for ceramic inductor according to any one of claims 1 to 4, characterized in that: The ceramic substrate comprises a mixture or a composite of Al2O3 and SiO2 with a particle size of 2 to 3 μm and a maximum particle size of ≤5 μm.
6. The marking material for ceramic inductor according to claim 5, characterized in that: The ceramic substrate also includes nano-sized silicon dioxide.
7. A method for manufacturing a marking material for a ceramic inductor according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: preparing raw materials for marking materials, including 15-25 wt% of ceramic substrate Al2O3, 20-30 wt% of SiO2, 6-12 wt% of organic auxiliary acrylic resin, 13-19 wt% of diethylene glycol butyl ether, 1-6 wt% of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 15-21 wt% of amorphous material containing B, Si, O and K, and 4-5 wt% of coloring material; S2: ball milling the mixed raw materials to obtain a marking material precursor, and the obtained marking material precursor is subjected to a subsequent sintering process to obtain a marking material.
8. The method for manufacturing a marking material for a ceramic inductor according to claim 7, characterized in that: In step S2, the marking material raw material is poured into a ball mill and ball milled to make the particle size D50 of the slurry ≤ 2.5 μm, and then dried and kept warm at 40° C. to 100° C. for 3 min to 20 min and then ground to obtain the marking material.
9. A ceramic inductor, characterized in that: A label made of the label material of the ceramic inductor according to any one of claims 1 to 6.
10. The ceramic inductor according to claim 9, characterized in that: A first identification layer is provided on the substrate layer on the upper surface of the inductor; The inner dielectric layer of the inductor corresponding to the first identification layer is provided with at least one intermediate identification layer; A second identification layer is provided on the substrate layer on the lower surface of the inductor corresponding to the middle identification layer; Among them, the substrate layer on the upper surface of the inductor provided with the first identification layer, the dielectric layer on the middle identification layer, and the substrate layer on the lower surface of the inductor provided with the second identification layer are combined, superimposed and sintered in sequence in the order of top, middle and bottom, so that the first identification layer, the middle identification layer and the second identification layer are combined to form an integrated identification pattern.
Citation Information
Patent Citations
Component identification method and structure
CN114218691A